Coevolutionary generative adversarial networks for medical image augumentation at scale - Flores, Diana; Toutouh-el-Alamin, Jamal; Hemberg, Erik; O’Reilly, Una-May (My University, 2022)
Medical image processing can lack images for diagnosis. Generative Adversarial Networks (GANs) provide a method to train generative models for data augmentation. Synthesized images can be used to improve the robustness of computer-aided diagnosis systems. However, GANs are difficult to train due to unstable training dynamics that may arise during the learning process, e.g., mode collapse and vanishing gradients. This paper focuses on Lipizzaner, a GAN training framework that combines spatial coevolution with gradient-based learning, which has been used to mitigate GAN training pathologies. Lipizzaner improves performance by taking advantage of its distributed nature and running at scale. Thus, the Lipizzaner algorithm and implementation robustness can be scaled to high-performance computing (HPC) systems to provide more accurate generative models. We address medical imaging data augmentation to create chest X-Ray images by using Lipizzaner on the HPC infrastructure provided by Oak Ridge National Labs' Summit Supercomputer. The experimental analysis shows improved performance by increasing the scale of the Lipizzaner GAN training. We also demonstrate that distributed coevolutionary learning improves performance even when using suboptimal neural network architectures due to hardware constraints.
Es un trabajo de investigación presentado durante el congreso internacional The Genetic and Evolutionary Computation Conference (GECCO 2022) en Boston.
Keywords: Fotografía médica; Generative adversarial networks; Coevolution; High performance computing; Medical imaging